UPAYA GURU MENINGKATKAN MINAT BELAJAR PESERTA DIDIK KELAS III DI SDN 04 TANJUNG PUTATTAHUN PELAJARAN 2023-2024 - Nura Rizqia; Suriadi Suriadi; Syaifudin Syaifudin (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study aims to describe: (1) Teachers' efforts to increase the learning interest of grade III students at SDN 04 Tanjung Putat. (2) Supporting and inhibiting factors for teachers' efforts to increase the learning interest of grade III students at SDN 04 Tanjung Putat. (3) Implications of teachers' efforts to increase the learning interest of grade III students at SDN 04 Tanjung Putat. This study is descriptive qualitative and the data collection techniques for this study are interviews, observations, and documentation. The results of the study show: (1) Teachers' efforts to increase the learning interest of grade III students at SDN 04 Tanjung Putat are by using various learning methods, providing learning media, providing reinforcement (praise or prizes) to students, taking an emotional approach to students, and carrying out activities that please students such as singing before carrying out the learning process to build a pleasant atmosphere. (2) Supporting and inhibiting factors for teachers' efforts to increase the learning interest of grade III students at SDN 04 Tanjung Putat consist of two factors: the first is internal factors originating from within the students, including student health and psychological factors such as student intelligence. secondly external factors, namely factors originating from outside the students such as the family environment, community environment and facilities available at school. (3) The implications of teacher efforts in increasing the learning interest of class III students at SDN 04 Tanjung Putat are the presence of a response or interest in learning. Students who are interested in following lessons will pay attention to the material presented by the teacher, actively ask or answer questions from the teacher, do not delay doing assignments, and when students are involved in learning, students will feel happy.